Sebaceous gland lipids - Picardo, Mauro (Landes Bioscience, 2009)
The principal activity of mature sebaceous glands is producing and secreting sebum, which is a complex mixture of lipids. Sebum composition is different among species and this difference is probably due to the function that sebum has to absolve. In human sebum there are unique lipids, such as squalene and wax esters not found anywhere else in the body nor among the epidermal surface lipids. Moreover, they correspond to major components supplying the skin with protection. However, the ultimate role of human sebum, as well the metabolic pathways regulating its composition and secretion rate, are far from a complete understanding. Increased sebum secretion is considered, among all features, the major one involved in the pathophysiology of acne. Along with increased sebum secretion rate, quali- and quantitative modifications of sebum are likely to occur in this pathology. Understanding the factors and mechanisms that regulate sebum production is needed in order to identify new targets that can be addressed to achieve a selective modulation of lipid biosynthesis as a novel therapeutic strategy to correct lipid disregulations in acne and other disorders of the pilosebaceous unit.